Integrating Islamic Values on ESL Classes: Indonesian Teachers' Attitudes Toward Islamic Education Management in South Thailand - Iswan; Zaitun (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research study was aimed to investigate ESL teachers' attitudes toward the policy of integrating Islamic values into their teachings. A total number of 32 ESL teachers who were hired as contract teachers teaching English at several different Islamic schools in South-Thailand participated as respondents. A set of 5-Likert scale questionnaire to measure the attitude of the respondents was the instrument used by the writers in collecting the data. A quantitative-descriptive method was applied in this study, in which the data were analyzed statistically before they were descriptively described. The findings of the statistical analysis revealed that most of the teachers have positive attitude (73.63%) toward this Islamic school management policy. The percentage was taken from 47% responses of the respondents on "Totally Agree" and 26.63% on "Agree" options. Thus, it can be concluded that most of ESL teachers who were teaching English at several Islamic schools in South Thailand had positive attitude towards the policy of integrating Islamic values into their teachings.